Lectures on Greek Philosophy 1928 - Anderson, John (Sydney University Press, 2008)
The Lectures on Greek Philosophy of 1928 are among the earliest lectures we have of John Anderson's, delivered in the year following his arrival in Sydney in 1927. In these teachings he closely and critically followed John Burnet's classic work Early Greek Philosophy.